THE EFFECT OF INDONESIA AND VIETNAM PARTNERSHIP COOPERATION ON INDONESIA'S PROCESSED FOOD INDUSTRY IN VIETNAM IN 2018-2019 - Pramana, Rizky; Waluyo, Tri Joko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This paper is a Bilateral Cooperation study which provides an analysis of cooperation between two countries in meeting needs and achieving common interests. This research is focused on the effect of Indonesia and partnership cooperation on Indonesia's processed food industry in Vietnam in 2018-2019. The industry is an industry that supports other industries and is interrelated with one another. The manufacturing industry is one of the sectors that contributes the largest GDP in Indonesia.This paper uses a qualitative research method that is descriptive and explanative, in which data is quoted from books, journals, mass media and websites. This research is supported by the level of analysis of the Nation State and Liberalism Perspective with the concept of International Cooperation where international cooperation is formed because of international life which includes various fields such as ideology, politics, economy, socio-culture, environment and defense and security. These problems have led countries in the world to establish international cooperation.The concept MoU on Cooperation between Indonesia and Vietnam is one of the national interests of the two countries, where in this bilateral cooperation the objective is to increase investment in Indonesia and Vietnam and eliminate various trade barriers between the two countries that have not been resolved. Therefore, investment and trade cooperation is cooperation to achieve the trade value stipulated in the Plan of Action of the two countries of USD 10 billion. Keywords: Effect, Partnership, Food, Trade, Industry, Manufacturing